2004
DOI: 10.1128/mcb.24.6.2277-2285.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clb6/Cdc28 and Cdc14 Regulate Phosphorylation Status and Cellular Localization of Swi6

Abstract: Nuclear export of the transcription factor Swi6 during the budding yeast Saccharomyces cerevisiae cell cycle is known to require phosphorylation of the Swi6 serine 160 residue. We show that Clb6/Cdc28 kinase is required for this nuclear export. Furthermore, Cdc28 combined with the S-phase cyclin Clb6 specifically phosphorylates serine 160 of Swi6 in vitro. Nuclear import of Swi6 occurs concomitantly with dephosphorylation of serine 160 in late M phase. We show that Cdc14 phosphatase, the principal effector of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 62 publications
1
81
0
Order By: Relevance
“…The Clb6/Cdc28 S-phase cell cycle kinase is responsible for phosphorylation of Swi6 on Ser160 (Geymonat et al 2004). Swi6 resides predominantly in the cytoplasm from late G1 until late M phase, at which time it relocalizes to the nucleus in response to dephosphorylation at Ser160, where it remains for most of G1.…”
Section: Control Of Swi6 Nucleocytoplasmic Shuttling By Mpk1mentioning
confidence: 99%
“…The Clb6/Cdc28 S-phase cell cycle kinase is responsible for phosphorylation of Swi6 on Ser160 (Geymonat et al 2004). Swi6 resides predominantly in the cytoplasm from late G1 until late M phase, at which time it relocalizes to the nucleus in response to dephosphorylation at Ser160, where it remains for most of G1.…”
Section: Control Of Swi6 Nucleocytoplasmic Shuttling By Mpk1mentioning
confidence: 99%
“…The pathway(s) responsible for cdc14 replication insufficiency can be potentially revealed through the identification of Cdc14-dependent events in the previous cell cycle. Incidentally, dephosphorylation of Swi6p (Ser-160) by Cdc14 is needed for its nuclear import in telophase (33) and formation of the SBF and MBF transciption complexes (34), which activate the G1 expression of a wide range of genes essential for S phase. Indeed, we found that several key SWI6-controlled genes involved in DNA replication and other processes showed reproducibly lower transcript levels in cdc14 in G1 (at 23°C), as well as 10 and 20 min into S phase (at 37°C) (Fig.…”
Section: G1 Transcription and Nuclear Import Defects In Cdc14 Impairmentioning
confidence: 99%
“…In the case of the early eluting peptide, we were unable to distinguish between phosphorylation at any of the first three residues. Because it is less likely that trypsin would efficiently cleave between Arg 3 and Thr 4 , we conclude that this sequence is most likely phosphorylated at Thr 5 . Phosphorylation at Ser 243 was found in several peptides due to the presence of multiple lysine and arginine residues at either end of the sequence surrounding it.…”
Section: Phosphate-dependent Phosphorylation Profile Of Pho4mentioning
confidence: 99%
“…It can serve as a recognition element, targeting a substrate for ubiquitin-dependent proteolysis (2), or serve as a docking site to recruit other proteins into multiprotein complexes (3). Phosphorylation can trigger a change in the three-dimensional structure of a protein or initiate translocation of the protein to another compartment of the cell (4). Disruption of normal cellular phosphorylation events is responsible for a number of human diseases (5).…”
mentioning
confidence: 99%